2015
DOI: 10.1177/0300060515579117
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive evaluation of renal oxygenation in primary nephrotic syndrome with blood oxygen level dependent magnetic resonance imaging: Initial experience

Abstract: Objectives: To use blood oxygen level dependent (BOLD) magnetic resonance imaging (MRI) to evaluate renal oxygenation in patients with primary nephrotic syndrome (PNS), and test the hypothesis that renal tissue oxygenation correlates with renal function, tubulointerstitial alterations and treatment response. Methods: Patients with untreated first-onset PNS and healthy control subjects underwent BOLD MRI. Blood and urine samples were obtained on the day of MRI, and patients underwent renal biopsy the day after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Some studies recommended the medulla-to-cortex ratio in R 2 * to be a more sensitive marker especially in diabetes, taking advantage of the disparate changes with disease severity in cortex vs. medulla [14]. Increased R 2 * in the cortex has been observed in chronic kidney disease (CKD) [19], with either minimal change or actually a reduction in medullary R 2 * [15,40,41]. The consensus among all respondents (Table 5; 82%) was that a novice BOLD researcher can obtain R 2 * measurements in both cortex and medulla using regions of interest (ROIs) drawn in collaboration with a radiologist.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies recommended the medulla-to-cortex ratio in R 2 * to be a more sensitive marker especially in diabetes, taking advantage of the disparate changes with disease severity in cortex vs. medulla [14]. Increased R 2 * in the cortex has been observed in chronic kidney disease (CKD) [19], with either minimal change or actually a reduction in medullary R 2 * [15,40,41]. The consensus among all respondents (Table 5; 82%) was that a novice BOLD researcher can obtain R 2 * measurements in both cortex and medulla using regions of interest (ROIs) drawn in collaboration with a radiologist.…”
Section: Discussionmentioning
confidence: 99%
“…However, assessment of renal oxygenation in vivo is still a challenge. Blood oxygen level-dependent (BOLD)-MRI is a novel, powerful, and a noninvasive technique, which can assess renal oxygenation [6,7]. The validity of BOLD-MRI in assessing renal tissue oxygenation is supported by direct measurements of tissue O 2 content by oxygen-sensitive microelectrodes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, BOLD MRI has been widely used to assess changes in renal oxygen level in various kidney disease conditions, for instance, ischemic [18], hypertensive [19], diabetic [20-23] and contrast [24-26] nephropathies as well as nephrotic syndrome [27], lupus nephritis [28, 29], chronic kidney disease [30-32], acute kidney injury [33, 34] and renal allograft rejection [35-39]. It is interesting to note that BOLD MRI studies with many analytical methods in patients with different etiologies have shown inconsistent and contradictory results, reporting higher or lower R2* values.…”
Section: Introductionmentioning
confidence: 99%